2018
DOI: 10.1111/jvh.12994
|View full text |Cite
|
Sign up to set email alerts
|

Screening haemodialysis patients for hepatitis C in Vietnam: The inconsistency between common hepatitis C virus serological and virological tests

Abstract: Selecting the appropriate screening method and interval for the early detection of hepatitis C virus (HCV) infection in low-resourced haemodialysis settings is a challenge. The challenge occurs when patients are classified as HCV-RNA positive but negative to HCV-core antigen (HCV-coreAg), anti-HCV and genotyping tests. We aim to clarify the inconsistency between HCV-RNA, HCV-coreAg, anti-HCV and HCV genotyping tests in haemodialysis patients and determine the reliability of HCV-coreAg as a routine two-monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This findings was in concordance with previous other study results. 10 The superiority of fourth-generation HCV (core Agantibody combined detection) assay-based studies over third-generation anti-HCV antibody detection is established in our research, as was found out by previous works. 13,31 Besides much better sensitivity and specificity, a 100% specificity vis-a-vis gold standard HCV RNA testing is noteworthy.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This findings was in concordance with previous other study results. 10 The superiority of fourth-generation HCV (core Agantibody combined detection) assay-based studies over third-generation anti-HCV antibody detection is established in our research, as was found out by previous works. 13,31 Besides much better sensitivity and specificity, a 100% specificity vis-a-vis gold standard HCV RNA testing is noteworthy.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings corroborate well with similar previous works. 10 Because genotype distribution can have a bearing on antibody-based test results, a kit covering (responding to) multiple genotypes is ideal for diagnostic purpose. 40,41 A Paris-based study found differing sensitivities of ELISA kits depending on HCV genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] The move away from anti-HCV toward HCV-coreAg screening is based on the need for accuracy, with experts suggesting that, while the nucleic acid testing (NAT) technique is superior to anti-HCV, it should be replaced with HCV-coreAg for routine monitoring of chronic hemodialysis patients because HCV-coreAg is more cost-effective, less labor-intensive, and comparable for accuracy. Half (56%, 9/16) of the studies reported exclusively on hemodialysis patients, and the majority (15/16) of publications were based in well-equipped tertiary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The information on prevalence and incidence rates of HCV among patients on regular dialysis in the emerging world is limited, and the most important survey to date has been given by the Asia-Pacific Dialysis Registry ( n = 201,590), which found that the prevalence of positive anti-HCV serologic status ranged between 0.7% and 18.1% across 10 various areas and regions [ 6 ]. Numerous single-center surveys from emerging countries have been published in the last decade, and these have reported high prevalence and incidence rates ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Epidemiology Of Hcv Infection In Dialysis Population and Recent Evidencementioning
confidence: 99%